The Effectiveness of a Training Program Based on the Universal Design for Learning in Improving the Teaching Competencies of Teachers of Students with Learning Difficulties in Al-Ahsa Governorate - Al-Rasheed, Wijdan Rashid; Melhem, Tareq Yousef Mustafa (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the effectiveness of a training program based on the principles of Universal Design for Learning (UDL) in improving teaching competencies for teachers of learning difficulties. The sample of the study consisted of (30) teachers of learning difficulties in public schools in Al-Ahsa Governorate. The study followed the semi-experimental approach with one group design. In order to answer the study questions, the researchers designed a scale of teaching competencies for the principles of UDL, which consisted of (40) items, and the training program based on the principles of UDL. After that, the study tools applied to the participants. The results revealed a statistically significant difference at the level of significance (0.01) between the mean scores of learning difficulties teachers in the two applications. The mean score of the pre-measurement was (86.50) and the mean score of the post-measurement was (96.40) in favor of post-measurement. The results also showed that there was no statistically significant difference at the level of significance (0.01) between the mean scores of learning difficulties teachers in the post-measurement and their mean scores in the follow-up measurement with a mean of (88.47), which shows the stability of the impact of the training program. The study recommends that professional development programs must be conducted before or in service to increase teachers’ knowledge of the UDL principles, insert the principles of UDL within the curricula and teacher preparation programs within the colleges of education. Also creating an educational environment that supports the application of teachers of students with learning difficulties to the principles of UDL in teaching, providing modern technologies and improving the quality and speed of the Internet in public schools.
Keywords: Universal design of learning; teachers of learning difficulties; teaching competencies; training program